Inductance device, preparation method thereof and electronic equipment
By adopting a double-layer magnetic powder structure, low-loss layer and high-saturation layer design in inductor devices, the eddy current heating problem of traditional copper magnetic co-burning inductors is solved, and higher saturation current and lower power consumption are achieved, and the inductor is improved Overall performance of the device.
Patent Information
- Application Number
- CN202411212069.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional copper magnetic co-fired inductors are difficult to achieve the optimal balance between high saturation current demand and low loss, resulting in serious eddy current heating and affecting overall performance.
Using a double-layer magnetic powder structure design, the low-loss layer and the high-saturation layer are composed of alloy metal or soft magnetic powder with a weight percentage of Fe content of 80-87% and 88-100% respectively, forming a coated on the core layer. The fill layer is achieved through the molding process, with the volume of low-loss layer accounting for 10%-90% and the volume of high-saturation layer accounting for 10%-90%.
Achieve higher saturation current while maintaining low power consumption, or lower power consumption at the same saturation current, effectively reducing eddy current heating and improving the performance of inductor devices.
Smart Images

Figure CN119207980A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inductor devices, and in particular to an inductor device and a preparation method thereof, and electronic equipment. Background Art
[0002] With the rapid development of renewable energy, mobile communications and robotics, modern electronic devices and systems have increasing performance requirements for power supplies and electronic components. Especially with the trend of thinning and high power of AI servers, high-end PCs, Pads, mobile phones and other devices, the size and power consumption requirements of the components used in the whole machine have become more stringent. The DC / DC circuit on the power supply side needs to achieve low power consumption while achieving high power output. This demand requires inductors to have higher efficiency and smaller size, which in turn promotes the continuous improvement and innovation of inductor performance.
[0003] Traditional inductor components, such as chip inductors, store and release energy through the principle of electromagnetic induction, playing a key role in filtering, voltage stabilization, energy storage and electromagnetic interference suppression. In this context, copper-magnetic co-firing has emerged as an important manufacturing process. This process combines the high conductivity of copper and the high energy storage capacity of magnetic materials. The copper-magnetic co-firing inductor produced has the advantages of high energy density, small footprint, high capacitance and low resistance.
[0004] The limitation of existing copper-magnetic co-fired inductor technology lies in the material properties of its soft magnetic powder, that is, it is difficult to achieve the best balance between high saturation current and low loss at the same time. In the manufacturing process of traditional copper-magnetic co-fired inductors, a single layer of evenly distributed magnetic powder filling is often used. This causes the inductor to be subjected to a large alternating field intensity when working, especially the material near the copper core, and the eddy current heating phenomenon is serious, which in turn affects the overall performance of the inductor. The demand for high saturation current is usually accompanied by higher energy loss, while the pursuit of low loss often comes at the expense of saturation current. This contradiction limits the further improvement of the performance of copper-magnetic co-fired inductors. Summary of the invention
[0005] The present application discloses an inductor device, a preparation method thereof and an electronic device. The inductor device uses low-loss alloy metal or soft magnetic powder as a low-loss layer filling material to reduce eddy current heating and loss; and a layer of high-saturation alloy metal or soft magnetic powder is pressed outside the low-loss layer to increase the saturation current of the inductor; the present application uses a double-layer magnetic powder structure design to enable the inductor device to achieve a higher saturation current while maintaining low power consumption, or have lower power consumption at the same saturation current.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The first object of the present application is to provide an inductor device, comprising:
[0008] Core layer;
[0009] A low-loss layer is coated on the outer surface of the core layer, and the two ends of the core layer extend outward to form terminal electrodes; the low-loss layer is an alloy metal or soft magnetic powder containing 80-87% by weight of Fe;
[0010] The high saturation layer is coated on the outer surface of the low loss layer, and the high saturation layer is an alloy metal or soft magnetic powder containing 88-100% by weight of Fe.
[0011] In some specific embodiments, the low-loss layer and the high-saturation layer form a filling layer coated on the core layer;
[0012] The volume of the low-loss layer accounts for 10% to 90% of the total volume of the filling layer, and the volume of the high-saturation layer accounts for 10% to 90% of the total volume of the filling layer.
[0013] In some specific embodiments, the low-loss layer includes the following chemical components in weight percentage:
[0014] Fe: 80-87%, Si: 1-9%, auxiliary chemical components: 4-19%.
[0015] In some specific embodiments, the auxiliary chemical component in the low-loss layer is at least one of Al, Cr, B, C, Nb, P, and O.
[0016] In some specific embodiments, when the auxiliary chemical component contains Al, the weight percentage of Al in the low-loss layer is: 0.5-8%;
[0017] When the auxiliary chemical component contains Cr, the weight percentage of Cr in the low-loss layer is: 0.5-8%;
[0018] When the auxiliary chemical component contains B, the weight percentage of B in the low-loss layer is: 0.5-8%;
[0019] When the auxiliary chemical component contains C, the weight percentage of C in the low-loss layer is: 0.5-8%;
[0020] When the auxiliary chemical component contains Nb, the weight percentage of Nb in the low-loss layer is: 0.5-8%;
[0021] When the auxiliary chemical component contains P, the weight percentage of P in the low-loss layer is: 0.1-5%;
[0022] When the auxiliary chemical component contains O, the weight percentage of O in the low-loss layer is 0.1-5%.
[0023] In some specific embodiments, the high saturation layer includes the following chemical components in weight percentage:
[0024] Fe: 88-100%, auxiliary chemical components: 0-12%.
[0025] In some specific embodiments, the auxiliary chemical component in the high saturation layer is at least one of Si, Al, Cr, Ni, B, C, P, and O.
[0026] In some specific embodiments, when the auxiliary chemical component contains Si, the weight percentage of Si in the high saturation layer is: 0.5-8%;
[0027] When the auxiliary chemical component contains Al, the weight percentage of Al in the high saturation layer is: 0.5-8%;
[0028] When the auxiliary chemical component contains Cr, the weight percentage of Cr in the high saturation layer is: 0.5-8%;
[0029] When the auxiliary chemical component contains B, the weight percentage of B in the high saturation layer is: 0.5-8%;
[0030] When the auxiliary chemical component contains C, the weight percentage of C in the high saturation layer is: 0.5-8%;
[0031] When the auxiliary chemical component contains P, the weight percentage of P in the high saturation layer is: 0.1-5%;
[0032] When the auxiliary chemical component contains O, the weight percentage of O in the high saturation layer is 0.1-5%.
[0033] In some specific implementations, the inductance value of the inductor device is 92-116nH (1MHz), the saturation current is 39-56A, and the temperature rise current is 34-42A.
[0034] In some specific embodiments, the core layer is any one of a copper core, an aluminum core, and a silver core.
[0035] In some embodiments, the high saturation layer is coated with a coating.
[0036] The second object of the present application is to provide a method for preparing an inductor device, comprising the following steps:
[0037] By molding, an alloy metal or soft magnetic powder containing 80-87% by weight of Fe is coated on the core layer to obtain a primary molded part;
[0038] By molding, the alloy metal or soft magnetic powder containing 88-100% by weight of Fe is coated on the primary molded part to obtain a secondary molded part;
[0039] The secondary molded part is subjected to heat treatment, lead-out terminal electrode treatment, and coating treatment in sequence to obtain an inductor device.
[0040] The third objective of the present application is to provide an electronic device comprising the inductor device described above.
[0041] The beneficial effects of this application are:
[0042] The inductor device described in the present application first coats a low-loss layer on the outside of the core layer, and then coats a high-saturation layer on the outside of the low-loss layer to form a double-layer magnetic powder structure. The design of the double-layer magnetic powder structure enables the inductor device to achieve a higher saturation current while maintaining low power consumption, or to have lower power consumption at the same saturation current. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0044] Figure 1 A cross-sectional side view of the inductor device described in the present application;
[0045] Figure 2 A cross-sectional front view of the inductor device described in this application;
[0046] Among them: 1. core layer; 2. filling layer; 21. low loss layer; 22. high saturation layer; 3. coating; 4. terminal electrode. DETAILED DESCRIPTION
[0047] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0048] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.
[0049] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.
[0050] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.
[0051] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. The manufacturer or concentration is not specified, and they are all analytically pure raw materials or reagents that can be routinely obtained. As long as the expected effect can be achieved, there is no particular restriction. The instruments and equipment used in the present embodiment are all purchased from major manufacturers in the market. As long as the expected effect can be achieved, there is no particular restriction. If specific techniques or conditions are not specified in the present embodiment, the techniques or conditions described in the literature in this area or according to the product specification are carried out.
[0052] In traditional copper-magnetic co-fired inductors, since the filling layer material is uniform and consistent, it is impossible to effectively deal with the eddy current heating problem caused by the inconsistent alternating field size in different parts, thus limiting the improvement of inductor performance; especially in the parts close to the copper core, due to the large alternating field, the eddy current heating is more serious, resulting in increased losses, which in turn affects the saturation current and overall performance of the inductor. In order to further increase the saturation current of the copper-magnetic co-fired inductor and reduce power consumption, the present application provides the following Figure 1-2 An inductor device as shown includes:
[0053] Core layer 1;
[0054] A low-loss layer 21 is coated on the outer surface of the core layer 1, and the two ends of the core layer extend outward to form terminal electrodes 4; the low-loss layer is an alloy metal or soft magnetic powder containing 80-87% by weight of Fe;
[0055] The high saturation layer 22 is coated on the outer surface of the low loss layer 21, and the high saturation layer is an alloy metal or soft magnetic powder containing 88-100% by weight of Fe.
[0056] It can be understood that in the low-loss layer, the Fe content is maintained in the range of 80-87%, which ensures that the low-loss layer has lower loss and good magnetic permeability.
[0057] Specifically, the low-loss layer is an alloy metal or soft magnetic powder containing 80-87% Fe by weight, for example, the Fe by weight is any value of 80%, 81%, 82%, 85%, or 87%, within the range of 80-87% (including the endpoint values).
[0058] More specifically, the alloy metal or soft magnetic powder containing 80-87% by weight of Fe is at least one of FeSiAl, FeSiBNbCu and FeSiB(C,Cr), that is, at least one of FeSiAl, FeSiBNbCu and FeSiB(C,Cr) is combined to obtain an Fe content of 80-87% by weight. The specific combination form or conditions can be adjusted according to actual conditions.
[0059] It can be understood that in the high saturation layer, Fe is the main component, and its high content (88-100%) provides a high saturation magnetic induction intensity, ensuring that the sample has good DC bias resistance, thereby being able to maintain stable performance at a larger current.
[0060] Specifically, the high saturation layer is an alloy metal or soft magnetic powder containing 88-100% Fe by weight, for example, the Fe by weight is any value of 88%, 91%, 92%, 95%, 100%, within 88-100% (including the endpoint values).
[0061] More specifically, the alloy metal or soft magnetic powder containing 88-100% by weight of Fe is at least one of Fe powder, FeSi, FeSiCr, and FeSiBPC; that is, at least one of Fe powder, FeSi, FeSiCr, and FeSiBPC is combined to obtain an alloy metal or soft magnetic powder containing 88-100% by weight of Fe. The specific combination form or conditions can be adjusted according to actual conditions.
[0062] It is understandable that in the process of electromagnetic induction of the inductor, the core layer is the key to energy transfer and conversion. In the present application, the core layer is any one of a copper core, an aluminum core, and a silver core.
[0063] In some embodiments, the low-loss layer 21 and the high-saturation layer 22 form a filling layer 2 coated on the core layer 1;
[0064] The volume of the low-loss layer accounts for 10% to 90% of the total volume of the filling layer, and the volume of the high-saturation layer accounts for 10% to 90% of the total volume of the filling layer.
[0065] More specifically, with a filling layer of 100 mm 3 For example, the volume range of the low-loss layer is 10-90mm 3 , the volume of the high saturation layer ranges from 10-90mm 3 ; When the volume of the low-loss layer is 10mm 3 The volume of the high saturation layer accounts for 90mm 3 ; When the volume of the low-loss layer is 90mm 3 , the volume proportion of the high saturation layer is 10mm 3 ; When the volume of the low-loss layer is 40mm 3 The volume of the high saturation layer accounts for 40mm 3 ; It can be adjusted and set according to actual needs, that is, the volume of the low-loss layer accounts for 10% to 90% of the total volume of the filling layer, and the volume of the high-saturation layer accounts for 10% to 90% of the total volume of the filling layer.
[0066] In some embodiments, the low-loss layer comprises the following chemical components in weight percentage:
[0067] Fe: 80-87%, Si: 1-9%, auxiliary chemical components: 4-19%.
[0068] It is understandable that the addition of Si (silicon) can improve the resistivity of the material and reduce eddy current loss; within the range of 1-9% Si, Si can effectively inhibit the formation of eddy currents and reduce the heating caused by eddy currents, thereby improving the efficiency of inductor devices. Auxiliary chemical composition can further adjust and optimize the electromagnetic properties of the material; for example, elements such as Al and Cr can improve the hardness and corrosion resistance of the material; elements such as B and C may help to form amorphous, improve the density and uniformity of the material; elements such as Nb can inhibit grain growth and obtain good nanocrystalline materials.
[0069] Specifically, the weight percentage of Si in the low-loss layer is 1-9%, for example, the weight percentage of Si is any value of 1%, 2%, 3%, 5%, 9%, within the range of 1-9% (including the endpoint values).
[0070] Specifically, the weight percentage of the auxiliary chemical components in the low-loss layer is 4-19%, for example, the weight percentage of Si is any value of 4%, 10%, 12%, 15%, 19%, within the range of 4-19% (including the endpoint values).
[0071] In some embodiments, the auxiliary chemical composition in the low-loss layer is at least one of Al, Cr, B, C, Nb, P, and O;
[0072] When the auxiliary chemical component contains Al, the weight percentage of Al in the low-loss layer is: 0.5-8%; specifically, the weight percentage of Al in the low-loss layer is 0.5-8%, for example, the weight percentage of Al is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0073] When the auxiliary chemical component contains Cr, the weight percentage of Cr in the low-loss layer is: 0.5-8%; specifically, the weight percentage of Cr in the low-loss layer is 0.5-8%, for example, the weight percentage of Cr is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0074] When the auxiliary chemical component contains B, the weight percentage of B in the low-loss layer is: 0.5-8%; specifically, the weight percentage of B in the low-loss layer is 0.5-8%, for example, the weight percentage of B is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within 0.5-8% (including the endpoint values).
[0075] When the auxiliary chemical component contains C, the weight percentage of C in the low-loss layer is: 0.5-8%; specifically, the weight percentage of C in the low-loss layer is 0.5-8%, for example, the weight percentage of C is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0076] When the auxiliary chemical component contains Nb, the weight percentage of Nb in the low-loss layer is: 0.5-8%; specifically, the weight percentage of Nb in the low-loss layer is 0.5-8%, for example, the weight percentage of Nb is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0077] When the auxiliary chemical component contains P, the weight percentage of P in the low-loss layer is: 0.1-5%; specifically, the weight percentage of P in the low-loss layer is 0.1-5%, for example, the weight percentage of P is any value of 0.1%, 1.0%, 2.8%, 3.5%, 5%, within 0.1-5% (including the endpoint values).
[0078] When the auxiliary chemical component contains O, the weight percentage of O in the low-loss layer is 0.1-5%. Specifically, the weight percentage of O in the low-loss layer is 0.1-5%, for example, the weight percentage of O is any value of 0.1%, 1.0%, 2.8%, 3.5%, 5%, within the range of 0.1-5% (including the endpoint values).
[0079] In some embodiments, the highly saturated layer includes the following chemical components in weight percentage:
[0080] Fe: 88-100%, auxiliary chemical components: 0-12%.
[0081] It is understandable that by adjusting the type and content of the auxiliary chemical components, the magnetic properties of the high saturation layer can be optimized, such as increasing the magnetic permeability, reducing the magnetic resistance, etc., thereby improving the saturation current and energy conversion efficiency of the inductor device.
[0082] Specifically, the weight percentage of the auxiliary chemical component in the high saturation layer is 0-12%, for example, the weight percentage of the auxiliary chemical component is any value of 0%, 1%, 2%, 5%, 12%, within the range of 0-12% (including the endpoint values).
[0083] In some embodiments, the auxiliary chemical component in the high saturation layer is at least one of Si, Al, Cr, Ni, B, C, P, and O.
[0084] When the auxiliary chemical component contains Si, the weight percentage of Si in the high saturation layer is: 0.5-8%; specifically, the weight percentage of Si in the high saturation layer is 0.5-8%, for example, the weight percentage of Si is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within 0.5-8% (including the endpoint values).
[0085] When the auxiliary chemical component contains Al, the weight percentage of Al in the high saturation layer is: 0.5-8%; specifically, the weight percentage of Al in the high saturation layer is 0.5-8%, for example, the weight percentage of Al is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0086] When the auxiliary chemical component contains Cr, the weight percentage of Cr in the high saturation layer is: 0.5-8%; specifically, the weight percentage of Cr in the high saturation layer is 0.5-8%, for example, the weight percentage of Cr is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0087] When the auxiliary chemical component contains B, the weight percentage of B in the high saturation layer is: 0.5-8%; specifically, the weight percentage of B in the high saturation layer is 0.5-8%, for example, the weight percentage of B is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0088] When the auxiliary chemical component contains C, the weight percentage of C in the high saturation layer is: 0.5-8%; specifically, the weight percentage of C in the high saturation layer is 0.5-8%, for example, the weight percentage of C is any value of 0.5%, 1.0%, 2.8%, 5.5%, 8%, within the range of 0.5-8% (including the endpoint values).
[0089] When the auxiliary chemical component contains P, the weight percentage of P in the high saturation layer is: 0.1-5%; specifically, the weight percentage of P in the high saturation layer is 0.1-5%, for example, the weight percentage of P is any value of 0.1%, 1.0%, 2.8%, 3.5%, 5%, within 0.1-5% (including the endpoint values).
[0090] When the auxiliary chemical component contains O, the weight percentage of O in the high saturation layer is 0.1-5%. Specifically, the weight percentage of O in the high saturation layer is 0.1-5%, for example, the weight percentage of O is any value of 0.1%, 1.0%, 2.8%, 3.5%, 5%, within 0.1-5% (including the endpoint values).
[0091] In some embodiments, the inductor device prepared in the present application has an inductance value of 92-116nH (1MHz), a saturation current of 39-56A, and a temperature rise current of 34-42A.
[0092] On the other hand, the present application provides a method for preparing an inductor device, comprising the following steps:
[0093] By molding, an alloy metal or soft magnetic powder containing 80-87% by weight of Fe is coated on the core layer to obtain a primary molded part;
[0094] By molding, the alloy metal or soft magnetic powder containing 88-100% by weight of Fe is coated on the primary molded part to obtain a secondary molded part;
[0095] The secondary molded part is subjected to heat treatment, lead-out terminal electrode treatment, and coating treatment in sequence to obtain an inductor device.
[0096] In the above-mentioned inductor device, the low-loss layer and the high-saturation layer form a filling layer, the outer surface of the core layer is covered with the low-loss layer, and the outer surface of the low-loss layer is covered with the high-saturation layer; the volume of the low-loss layer accounts for 10% to 90% of the total volume of the filling layer, and the volume of the high-saturation layer accounts for 10% to 90% of the total volume of the filling layer.
[0097] Specifically, the molding process of the primary molded parts and the secondary molded parts in the preparation method is: preparing a core layer, an alloy metal or soft magnetic powder containing 80-87% by weight of Fe, an alloy metal or soft magnetic powder containing 88-100% by weight of Fe, a mold, an adhesive (if necessary) and other necessary auxiliary materials. The core layer is placed at the center of the mold to ensure accurate positioning; an appropriate amount of alloy metal or soft magnetic powder containing 80-87% by weight of Fe is filled into the mold cavity around the copper core, and compression molding is performed using appropriate pressure to make the alloy metal or soft magnetic powder containing 80-87% by weight of Fe fit tightly around the copper core to form a low-loss layer, thereby obtaining a primary molded part containing a low-loss layer; the outside of the primary molded part is filled with alloy metal or soft magnetic powder containing 88-100% by weight of Fe, and compression molding is performed using appropriate pressure to make the alloy metal or soft magnetic powder containing 88-100% by weight of Fe fit tightly around the primary molded part to form a high-saturation layer, thereby obtaining a secondary molded part containing a high-saturation layer.
[0098] It is understandable that in the present application, the inductor can be prepared in an integrated manner through the compression molding process, avoiding the assembly process of multiple independent components, improving production efficiency and reducing production costs. Moreover, through compression molding, the material is subjected to uniform pressure in the mold cavity, which helps to reduce the hysteresis loss and eddy current loss caused by uneven material distribution or gaps; the inductor after compression molding has a more uniform internal structure and a more reasonable air gap distribution, which can effectively reduce vibration noise and electromagnetic interference and improve overall performance.
[0099] Specifically, the secondary molded part is heat treated according to conventional processes; the core layer of the heat-treated secondary molded part is bent and used as a lead-out terminal electrode 4; the secondary molded part containing the terminal electrode is coated (using epoxy resin) according to conventional processes to form a coating 3 on the surface of the secondary molded part.
[0100] It is understood that the secondary molded part is annealed in a specific atmosphere (such as nitrogen) to further release stress and improve the magnetic properties and physical properties of the material. The secondary molded part with the terminal electrode is led out, and the outer surface of the secondary molded part can also be coated with a protective material such as epoxy resin to improve the weather resistance and reliability of the device.
[0101] In addition, the present application also provides an electronic device, including the above-mentioned inductor device; the electronic device can be an AI server, a computer, a mobile phone, or other electronic device containing an inductor device.
[0102] The following is a further description of an inductor device of the present invention in conjunction with a specific embodiment:
[0103] Example 1
[0104] An inductor device comprises a copper core, wherein the copper core is coated by a filling layer; a low-loss layer and a high-saturation layer are arranged in the filling layer; the outer surface of the copper core is coated with the low-loss layer, and the outer surface of the low-loss layer is coated with the high-saturation layer; the material forming the low-loss layer is a FeSiAl soft magnetic composite material (Fe weight content is 85%, Si weight content is 9%, Al weight content is 6%), and the low-loss layer accounts for 70% of the volume of the filling layer; the material forming the high-saturation layer is a FeSi soft magnetic composite material (Fe weight content is 95.5%, Si weight content is 4.5%), and this high-saturation material layer accounts for 30% of the volume of the filling layer.
[0105] Comparative Example 1
[0106] An inductor device comprises a copper core which is coated by a filling layer; the filling layer has only one layer and the filling layer material is a FeSiAl soft magnetic composite material (Fe weight content is 85%, Si weight content is 9%, Al weight content is 6%).
[0107] Comparative Example 2
[0108] An inductor device comprises a copper core which is coated by a filling layer. The filling layer has only one layer and is formed of a FeSi soft magnetic composite material (Fe content is 95.5% by weight and Si content is 4.5% by weight).
[0109] After testing, the inductor device prepared in Example 1 has an inductance value of 98nH (1MHz), a saturation current of 50A, a temperature rise current of 42A, and better comprehensive electrical performance.
[0110] The inductance value of the inductor device in comparative example 1 is 105nH (1MHz), the saturation current is 36A, and the temperature rise current is 43A; the inductance value of the inductor device in comparative example 2 is 87nH (1MHz), the saturation current is 56A, and the temperature rise current is 31A. It is difficult to balance the saturation current and the temperature rise current at the same time.
[0111] Example 2
[0112] An inductor device comprises a copper core, wherein the copper core is coated by a filling layer; a low-loss layer and a high-saturation layer are arranged in the filling layer; the outer surface of the copper core is coated with the low-loss layer, and the outer surface of the low-loss layer is coated with the high-saturation layer; the material forming the low-loss layer is a FeSiAl soft magnetic composite material (Fe weight content is 86%, Si weight content is 9%, Al weight content is 5%), and the low-loss layer accounts for 50% of the volume of the filling layer; the material forming the high-saturation layer is a FeSiCr soft magnetic composite material (Fe weight content is 92%, Si weight content is 3.5%, Cr weight content is 4.5%), and this high-saturation material layer accounts for 50% of the volume of the filling layer.
[0113] Comparative Example 3
[0114] An inductor device comprises a copper core, wherein the copper core is coated with a filling layer; the filling layer has only one layer, and the material forming the filling layer is a mixture of a FeSiAl soft magnetic composite material and a FeSiCr soft magnetic composite material, and the volume ratio of the two materials is 1:1. The Fe weight content of the FeSiAl soft magnetic composite material is 86% by weight, the Si weight content is 9% by weight, and the Al weight content is 5% by weight; the Fe weight content of the FeSiCr soft magnetic composite material is 92% by weight, the Si weight content is 3.5% by weight, and the Cr weight content is 4.5%.
[0115] Comparative Example 4
[0116] An inductor device comprises a copper core, wherein the copper core is coated with a filling layer; the filling layer has only one layer, and the material forming the filling layer is a FeSiAl soft magnetic composite material. The Fe weight content of the FeSiAl soft magnetic composite material is 86%, the Si weight content is 9%, and the Al weight content is 5%;
[0117] Comparative Example 5
[0118] An inductor device includes a copper core, wherein the copper core is covered by a filling layer; the filling layer has only one layer, and the material forming the filling layer is a FeSiCr soft magnetic composite material. The FeSiCr soft magnetic composite material contains 92% by weight of Fe, 3.5% by weight of Si, and 4.5% by weight of Cr.
[0119] After testing, the inductor device prepared in Example 2 has an inductance value of 116nH (1MHz), a saturation current of 56A, and a temperature rise current of 38A. The saturation current is higher and the temperature rise current is higher.
[0120] The inductance value of the inductor device in comparative example 3 is 115nH (1MHz), the saturation current is 44A, and the temperature rise current is 31A; the inductance value of the inductor device in comparative example 4 is 103nH (1MHz), the saturation current is 43A, and the temperature rise current is 41A; the inductance value of the inductor device in comparative example 5 is 129nH (1MHz), the saturation current is 59A, and the temperature rise current is 30A.
[0121] Example 3
[0122] An inductor device comprises a copper core, wherein the copper core is coated by a filling layer; a low-loss layer and a high-saturation layer are arranged in the filling layer; the outer surface of the copper core is coated with the low-loss layer, and the outer surface of the low-loss layer is coated with the high-saturation layer; the material forming the low-loss layer is a FeSiBNbCu soft magnetic composite material, and the low-loss layer accounts for 40% of the volume of the filling layer; the material forming the high-saturation layer is a FeSiBPC soft magnetic composite material, and the high-saturation material layer accounts for 60% of the volume of the filling layer;
[0123] Among them, in the FeSiBNbCu soft magnetic composite material, the weight content of Fe is 80%, the weight content of Si is 1%, the weight content of Nb is 8%, the weight content of B is 8%, and the weight content of Cu is 3%; in the FeSiBPC soft magnetic composite material, the weight content of Fe is 88%, the weight content of Si is 0.5%, the weight content of B is 4%, the weight content of P is 2.5%, and the weight content of C is 5%.
[0124] Comparative Example 6
[0125] An inductor device includes a copper core, which is coated with a filling layer; the filling layer has only one layer, and the material forming the filling layer is a FeSiBNbCu soft magnetic composite material. In the FeSiBNbCu soft magnetic composite material, the weight content of Fe is 80%, the weight content of Si is 1%, the weight content of Nb is 8%, the weight content of B is 8%, and the weight content of Cu is 3%.
[0126] Comparative Example 7
[0127] An inductor device includes a copper core, wherein the copper core is coated with a filling layer; the filling layer has only one layer, and the material forming the filling layer is a FeSiBPC soft magnetic composite material. In the FeSiBPC soft magnetic composite material, the Fe weight content is 88%, the Si weight content is 0.5%, the B weight content is 4%, the P weight content is 2.5%, and the C weight content is 5%.
[0128] After testing, the inductor device prepared in Example 3 has an inductance value of 105nH (1MHz), a saturation current of 52A, and a temperature rise current of 40A.
[0129] The inductance value of the inductor device in Comparative Example 6 is 108nH (1MHz), the saturation current is 41A, and the temperature rise current is 44A; the inductance value of the inductor device in Comparative Example 7 is 101nH (1MHz), the saturation current is 55A, and the temperature rise current is 32A.
[0130] Example 4
[0131] An inductor device comprises a copper core, wherein the copper core is coated by a filling layer; a low-loss layer and a high-saturation layer are arranged in the filling layer; the outer surface of the copper core is coated with the low-loss layer, and the outer surface of the low-loss layer is coated with the high-saturation layer; the material forming the low-loss layer is a FeSiAl soft magnetic composite material (Fe weight content is 85%, Si weight content is 9%, Al weight content is 6%), and the low-loss layer accounts for 10% of the volume of the filling layer; the material forming the high-saturation layer is a FeSi soft magnetic composite material (Fe weight content is 95.5%, Si weight content is 4.5%), and this high-saturation material layer accounts for 90% of the volume of the filling layer.
[0132] After testing, the inductor device prepared in Example 4 has an inductance value of 92nH (1MHz), a saturation current of 53A, and a temperature rise current of 34A.
[0133] Example 5
[0134] An inductor device comprises a copper core, wherein the copper core is coated by a filling layer; a low-loss layer and a high-saturation layer are arranged in the filling layer; the outer surface of the copper core is coated with the low-loss layer, and the outer surface of the low-loss layer is coated with the high-saturation layer; the material forming the low-loss layer is a FeSiAl soft magnetic composite material (Fe weight content is 85%, Si weight content is 9%, Al weight content is 6%), and the low-loss layer accounts for 90% of the volume of the filling layer; the material forming the high-saturation layer is a FeSi soft magnetic composite material (Fe weight content is 95.5%, Si weight content is 4.5%), and this high-saturation material layer accounts for 10% of the volume of the filling layer.
[0135] After testing, the inductor device prepared in Example 5 has an inductance value of 102nH (1MHz), a saturation current of 39A, and a temperature rise current of 40A.
[0136] From the above-mentioned embodiments 1-5, it can be seen that the present application has flexibility and adjustability in the design of the double-layer magnetic powder structure. By adjusting the chemical composition and volume of the low-loss layer and the high-saturation layer, the performance of the inductor device can be optimized in different application scenarios.
[0137] At the same time, the present application effectively solves the problem of increased losses due to the larger alternating field and more serious eddy current heating in the area close to the copper core through the design of a double-layer magnetic powder structure, allowing the inductor device to achieve a higher saturation current while maintaining low power consumption, or have lower power consumption at the same saturation current.
[0138] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. An inductor device, characterized in that: include: Core layer; A low-loss layer is coated on the outer surface of the core layer, and the two ends of the core layer extend outward to form terminal electrodes; the low-loss layer is an alloy metal or soft magnetic powder containing 80-87% by weight of Fe; The high saturation layer is coated on the outer surface of the low loss layer, and the high saturation layer is an alloy metal or soft magnetic powder containing 88-100% by weight of Fe.
2. The inductor device according to claim 1, characterized in that: The low-loss layer and the high-saturation layer form a filling layer coated on the core layer; The volume of the low-loss layer accounts for 10% to 90% of the total volume of the filling layer, and the volume of the high-saturation layer accounts for 10% to 90% of the total volume of the filling layer.
3. The inductor device according to claim 1, characterized in that: The low-loss layer comprises the following chemical components in weight percentage: Fe: 80-87%, Si: 1-9%, auxiliary chemical components: 4-19%.
4. The inductor device according to claim 3, characterized in that: The auxiliary chemical component in the low-loss layer is at least one of Al, Cr, B, C, Nb, P, and O.
5. The inductor device according to claim 4, characterized in that: When the auxiliary chemical component contains Al, the weight percentage of Al in the low-loss layer is: 0.5-8%; When the auxiliary chemical component contains Cr, the weight percentage of Cr in the low-loss layer is: 0.5-8%; When the auxiliary chemical component contains B, the weight percentage of B in the low-loss layer is: 0.5-8%; When the auxiliary chemical component contains C, the weight percentage of C in the low-loss layer is: 0.5-8%; When the auxiliary chemical component contains Nb, the weight percentage of Nb in the low-loss layer is: 0.5-8%; When the auxiliary chemical component contains P, the weight percentage of P in the low-loss layer is: 0.1-5%; When the auxiliary chemical component contains O, the weight percentage of O in the low-loss layer is 0.1-5%.
6. The inductor device according to claim 1, characterized in that: The highly saturated layer comprises the following chemical components in weight percentage: Fe: 88-100%, auxiliary chemical components: 0-12%.
7. The inductor device according to claim 6, characterized in that: The auxiliary chemical component in the high saturation layer is at least one of Si, Al, Cr, Ni, B, C, P, and O.
8. The inductor device according to claim 6, characterized in that: When the auxiliary chemical component contains Si, the weight percentage of Si in the high saturation layer is: 0.5-8%; When the auxiliary chemical component contains Al, the weight percentage of Al in the high saturation layer is: 0.5-8%; When the auxiliary chemical component contains Cr, the weight percentage of Cr in the high saturation layer is: 0.5-8%; When the auxiliary chemical component contains B, the weight percentage of B in the high saturation layer is: 0.5-8%; When the auxiliary chemical component contains C, the weight percentage of C in the high saturation layer is: 0.5-8%; When the auxiliary chemical component contains P, the weight percentage of P in the high saturation layer is: 0.1-5%; When the auxiliary chemical component contains O, the weight percentage of O in the high saturation layer is 0.1-5%.
9. An inductor device according to any one of claims 1 to 8, characterized in that: The inductance value of the inductor device is 92-116nH (1MHz), the saturation current is 39-56A, and the temperature rise current is 34-42A.
10. An inductor device according to any one of claims 1 to 8, characterized in that: The core layer is any one of a copper core, an aluminum core and a silver core.
11. The inductor device according to claim 1, characterized in that: The high saturation layer is coated with a coating layer.
12. A method for preparing an inductor device, characterized in that: The following steps are involved: By molding, an alloy metal or soft magnetic powder containing 80-87% by weight of Fe is coated on the core layer to obtain a primary molded part; By molding, the alloy metal or soft magnetic powder containing 88-100% by weight of Fe is coated on the primary molded part to obtain a secondary molded part; The secondary molded part is subjected to heat treatment, lead-out terminal electrode treatment, and coating treatment in sequence to obtain an inductor device.
13. An electronic device, characterized in that: The invention comprises the inductor device according to any one of claims 1 to 11 or the inductor device prepared by the preparation method according to claim 12.
